2020
DOI: 10.1158/1078-0432.ccr-20-0587
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial of 68Ga-PSMA and 18F-FDG PET/CT in Nonmetastatic Prostate Cancer Patients with an Early PSA Progression During Castration

Abstract: ◥Purpose: Tumor heterogeneity and burden, which impact treatment outcome in prostate cancer, are rarely evaluated using nextgeneration imaging.Experimental Design: The trial prospectively included 37 patients who had an early PSA progression (≤2 ng/mL) during castration and high-risk (PSA doubling time ≤10 months) nonmetastatic disease by conventional imaging. All patients underwent both 68 Ga-PSMA and 18 F-FDG PET/CT. Lesions were classified into PSMAþFDGAE lesions and PSMA-FDGþ lesions. The primary endpoint … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…Our analysis showed that FDG+/PSMA− lesions occurred in one third (33%) of patients with mCRPC prior to RLT, which is in line with a recent study by Wang et al (33%) [19], and slightly higher compared to the results of Hofmann et al (19%) [14]. FDG+/PSMA− lesions were found in skeleton or liver in 44% of cases, which was comparable to prior results in the study of Thang et al (50% or 38%, respectively) [16].…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis showed that FDG+/PSMA− lesions occurred in one third (33%) of patients with mCRPC prior to RLT, which is in line with a recent study by Wang et al (33%) [19], and slightly higher compared to the results of Hofmann et al (19%) [14]. FDG+/PSMA− lesions were found in skeleton or liver in 44% of cases, which was comparable to prior results in the study of Thang et al (50% or 38%, respectively) [16].…”
Section: Discussionsupporting
confidence: 93%
“…Before quantification of PSMA uptake can be used as a biomarker or surrogate endpoint to identify response to treatment, and before we can design sufficiently powered response evaluation studies, a thorough understanding of parameters affecting the quantitative results is required. Uptake of FDG and PSMA differ due to pharmacodynamical differences [ 8 , 9 , 10 ]. Therefore, comparison of uptake measurements from scans with different ligands should be approached with caution.…”
Section: Introductionmentioning
confidence: 99%
“…While traditionally used to exclude other sites or sources of metastatic disease, FDGPET has improved disease characterisation in hormone-naïve PC and CRPC. 4 For CRPC, the addition of FDG PET after PSMA PET increased the detection of nodal or distant metastases from 65% to 73% in men with high risk CRPC and no metastasis on conventional imaging with CT and bone scan. Furthermore, patterns of PSMA and FDG PET uptake may inform eligibility for RLT 5 so FDG PET uptake may further assist with patient selection for MDT.…”
Section: Discussionmentioning
confidence: 99%